2012
DOI: 10.1021/jp304187v
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Surface Reactivity of WO42–, SO42–, PO43– Modified Ca-Hydroxyapatite Catalysts and Their Activity in Ethanol Conversion

Abstract: In the current study, we have synthesized calcium hydroxyapatite (CaHAP) from different phosphorus sources namely, NH 4 H 2 PO 4 and H 3 PO 4 . The structure of CaHAP was confirmed by XRD, FT-IR, and Raman characterization methods. The CaHAP was further modified with various anions such as WO 4 2− , SO 4 2−, and PO 4 3− with fixed content of 10 wt %. To understand the textural and structural properties, these samples were thoroughly characterized by N 2 physisorption, X-ray diffraction, Fourier transform infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Raman and 31 P NMR spectroscopic techniques are commonly used to discriminate between the different calcium phosphates phases . From the Raman spectra reported in Figure (A), all the samples exhibit the typical band at 960 cm –1 assigned to the ν 1 vibration mode of phosphate groups (PO 4 3– ) of the hydroxyapatite structure . In the same way, all 31 P NMR spectra reported in Figure (B), reveal a main intense line centered at 2.9 ppm, which is also characteristic of bulk PO 4 3– of hydroxyapatites…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Raman and 31 P NMR spectroscopic techniques are commonly used to discriminate between the different calcium phosphates phases . From the Raman spectra reported in Figure (A), all the samples exhibit the typical band at 960 cm –1 assigned to the ν 1 vibration mode of phosphate groups (PO 4 3– ) of the hydroxyapatite structure . In the same way, all 31 P NMR spectra reported in Figure (B), reveal a main intense line centered at 2.9 ppm, which is also characteristic of bulk PO 4 3– of hydroxyapatites…”
Section: Resultsmentioning
confidence: 77%
“…Beyond phase identification and the crystallinity description provided by XRD, techniques such as IR, Raman, and NMR spectroscopy are useful tools to investigate local organization of the various species building up the HAp structure. Indeed, these characterization techniques are used in a complementary manner to provide qualitative and semiquantitative data not only on the structural hydroxyl (OH – ) and phosphate (PO 4 3– ) groups, which are the main components of the apatitic framework, but also on the presence of additional species possibly substituted within the structure, such as hydrogenphosphate (HPO 4 2– ) or carbonate (CO 3 2– ) groups,[11a], as illustrated by the typical IR DRIFT spectrum recorded at 623 K at the end of the in situ thermal pretreatment that is reported in Figure . Notably, compared with reported FTIR spectra, which are usually recorded at room temp., the band positions observed in the DRIFT spectra recorded at 623 K (see Exp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to identify the catalytically active sites on HAP have relied largely on spectroscopic studies. 26,27,28,29 Diallo-Garcia et al have observed the existence of basic OH -, O 2and PO4 3groups through FTIR of adsorbed CO2. 26,27 Further studies by these authors using acetylene as a probe have revealed an additional acid-base (POH-OH) pair.…”
Section: Introductionmentioning
confidence: 99%
“…These cations are coordinated to 6 phosphate oxygens and 1 oxygen belonging to a hydroxyl group [43,47]. ) [42,56], and OHreplacement (F -, Cl -) [43].…”
Section: -mentioning
confidence: 99%